The Use of Problem-Based Learning (PBL) in Teaching Speaking to the Seventh-Grade Students at Mts NWDI Pangsor Gunung - Usuluddin; Husnu, Muhammad; Selasih, Rini Dian; Wati, Laela (PROJECT (Professional Journal of English Education), 2026)
This study aims to explore the implementation of Problem-Based Learning (PBL) in speaking classes and to examine its effectiveness in improving the speaking skills of seventh-grade students at MTs NWDI Pangsor Gunung. A pre-experimental design and a quantitative approach have been used in the present research. The sample consisted of 18 seventh-grade students who participated in PBL lessons. Pre- and post-test speaking assessments were used to gather information on speaking abilities. The average score on the preliminary test was 55.38, and the average score on the post-test was 66.88. After PBL was implemented, students' speaking abilities significantly improved, as indicated by the paired sample t-test's significance score (p-value) of 0.000 < 0.05. Thus, it can be concluded that the implementation of Problem-Based Learning has a positive and significant effect on improving the speaking skills of seventh-grade students at MTs NWDI PangsorGunung. Therefore, it is recommended that teachers use PBL as an effective speaking learning method at the junior high school level.